Theoretical study on the electronic structure and photophysical properties of a series of iridium(III) complexes bearing non-planar tetradentate chelate and substituted bipyrazolate chelate ligands. (15th July 2020) - Wang, Qingshuang; Zhao, Lihui; Han, Deming
Graphical abstract: The electronic structure and photophysics properties of a series of iridium(III) complexes bearing non-planar tetradentate chelate and substituted bipyrazolate chelate ligands have been theoretically investigated. Abstract: Density functional theory (DFT) and time-dependent density functional theory (TDDFT) calculations have been adopted to investigate a series of iridium(III) complexes with different electron-accepting and electron-donating substituents (CF3, CN, H, CH3 and N(CH3 )2 ). All the studied complexes have distorted octahedral structures around the Ir(III) metal center with the d 6 configuration. The HOMO and LUMO distributions for all the studied complexes are mainly localized on the bipz and L ligands, respectively. The ionization potential and electron affinity have been calculated to evaluate the injection abilities of the holes and electrons in these studied complexes. The calculated lowest energy emissions using the TDDFT/M062X method are located at 498, 502, 445, 477 and 600 nm, respectively. The theoretical results show that these different substituents have different effects on the electronic structure and photophysical properties. This study can be useful for the design of potential blue phosphorescent organic light-emitting diode (OLED) materials.